A multistate model for correlated interval‐censored life history data in caries research. Issue 2 (26th September 2016) - Pak, Daewoo; Li, Chenxi; Todem, David; Sohn, Woosung
Summary: We propose a three‐state frailty Markov model coupled with likelihood‐based inference to analyse tooth level life course data in caries research. This analysis is challenging because of intraoral clustering, interval censoring, multiplicity of caries states and computational complexities. We also develop a Bayesian approach to predict future caries transition probabilities given observed life history data. Numerical experiments demonstrate that the methods proposed perform very well in finite samples with moderate sizes. The practical utility of the model is illustrated by using life course data from a unique longitudinal study of dental caries in young low income urban African‐American children. In this analysis, we evaluate for any spatial symmetry in the mouth with respect to the life course of dental caries, and whether the same type of tooth has a similar decay process in boys and girls.